2003
DOI: 10.1074/jbc.m212500200
|View full text |Cite
|
Sign up to set email alerts
|

The Adhesion and Differentiation-inhibitory Activities of the Immunoglobulin Superfamily Member, Carcinoembryonic Antigen, Can Be Independently Blocked

Abstract: The external domains of Ig superfamily members are involved in multiple binding interactions, both homophilic and heterophilic, that initiate molecular events leading to the execution of diverse cell functions. Human carcinoembryonic antigen (CEA), an Ig superfamily cell surface glycoprotein used widely as a clinical tumor marker, undergoes homophilic interactions that mediate intercellular adhesion. Recent evidence supports the view that deregulated overexpression of CEA has an instrumental role in tumorigene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
46
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 34 publications
0
46
0
Order By: Relevance
“…14 Fluorescence-activated cell sorting (FACS) expression profiles were then obtained by treatment of cell suspensions with 16 mg/ml humanized MN-14 or 100 mg/ml anti-CEA mAb J22 or no primary antibody (control) followed by fluorescein (FITC)-conjugated secondary antibody, and analyzed using a Becton Dickinson FACScan instrument, as described previously. 14 …”
Section: Testing Of Mn-14 Epitope Locationmentioning
confidence: 99%
“…14 Fluorescence-activated cell sorting (FACS) expression profiles were then obtained by treatment of cell suspensions with 16 mg/ml humanized MN-14 or 100 mg/ml anti-CEA mAb J22 or no primary antibody (control) followed by fluorescein (FITC)-conjugated secondary antibody, and analyzed using a Becton Dickinson FACScan instrument, as described previously. 14 …”
Section: Testing Of Mn-14 Epitope Locationmentioning
confidence: 99%
“…3), two regions of sequence variability (V-regions) were detected. Moreover, these V-regions were located adjacent to or within the regions corresponding to binding sites identified previously for opa proteins (55,56) and MHV (57-59) and adhesive domains mediating intercellular adhesion (25,28,33) (Fig. 3).…”
Section: Sequence Alignment Delineates Groups Of N-domains In Rat Andmentioning
confidence: 99%
“…Epitope B Is Located within the Major Adhesive Site in the CEACAM1 a N-domain-In previous reports (25,28,33,(55)(56)(57)(58)(59), the adhesive sites for CEA and the binding domains for MHV and opa proteins were localized to the C ␤-strand and CCЈ loop domains. Because one of the mAb epitopes was within this region, it was of interest to determine whether the two mAbs could block cell adhesion.…”
Section: Sequence Alignment Delineates Groups Of N-domains In Rat Andmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that essentially all CEA family members, including GPIanchored CEA and CEACAM6, function as homotypic intercellular adhesion molecules in vitro (Benchimol et al, 1989;Oikawa et al, 1989;Stanners and Fuks, 1998). In contrast with the transmembrane member CEACAM1 (Eidelman et al, 1993;Rojas et al, 1996;Ilantzis et al, 2002;Taheri et al, 2003), CEA and CEACAM6 overexpression inhibits cell differentiation and anoikis in vitro (Eidelman et al, 1993;Ordonez et al, 2000;Screaton et al, 2000;Soeth et al, 2001;Taheri et al, 2003;Duxbury et al, 2004) and in vivo (Chan et al, unpublished results). The structural requirements for the inhibitory effects of CEA on differentiation were demonstrated to depend critically on the CEA-specific GPI anchor attached to self-binding extracellular domains Taheri et al, 2003).…”
Section: Introductionmentioning
confidence: 99%